1957
DOI: 10.1152/ajplegacy.1957.191.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local X-Irradiation on Albumen Formation by the Hen's Oviduct

Abstract: X-irradiation of the surgically exposed oviduct of the hen reduces the formation of albumen dry matter (which is composed essentially of protein). Over a dosage range of 0–4000 r, the irradiation effect is logarithmically related to the dose, with the albumen (dry basis) formation being reduced 40% at 4000 r. At higher doses (5000 r) irreversible changes apparently take place, since very few birds so treated return to egg production. Radioinhibition of albumen formation requires direct irradiation of the ovidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These workers showed that ovalbumin and conalbumin are formed at the same rate and that the site of formation is in the oviduct as was suggested by the earlier work of Smith, Winget and Hague (1957).…”
Section: R Eports In the Literature Indicatementioning
confidence: 54%
“…These workers showed that ovalbumin and conalbumin are formed at the same rate and that the site of formation is in the oviduct as was suggested by the earlier work of Smith, Winget and Hague (1957).…”
Section: R Eports In the Literature Indicatementioning
confidence: 54%